Strategi Peningkatan Pendapatan Pedagang Kaki Lima (PKL) dengan Analisis Business Model Canvas (Studi Kasus: Pedagang Kaki Lima Lapangan Kantin Wirabraja di Bukittinggi) - Tania Octavia; Andis Febrian (Global Leadership Organizational Research in Management, 2024)
The economic sector is currently experiencing rapid development, including the informal business sector that aims to fulfil the needs of life. Street vendors (PKL) are included in this sector with small capital and businesses that are private or group, utilising the crowd. Along with economic development, competition among street vendors is getting tighter, including in the Wirabraja canteen field, Bukittinggi, the majority of which are engaged in the culinary sector and children's entertainment. This study aims to determine the strategies to increase income and the obstacles faced by street vendors using Business Model Canvas (BMC) analysis. This research is descriptive qualitative with data collection methods through observation, interviews, and documentation. The results showed that Wirabraja canteen field vendors already know the strategy of increasing income and overcoming natural obstacles such as weather by bringing their own equipment. Income generation strategies are analysed through two important elements of BMC, namely Customer Segments and Customer Relationships.